2021
DOI: 10.36987/ecobi.v8i1.2078
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Frekuensi Perdagangan, Volume Perdagangan, Dan Kapitalisasi Pasar Terhadap Return Saham Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2016-2019

Abstract: This study aims to determine the impact of Trading Frequency, Trading Volume, and Market Capitalization on the stock returns of Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2019 Period. The nature of this research is quantitative explanatory. The population is manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The research sample of 18 manufacturing companies that are still listed on the Indonesia Stock Exchange with the sampling technique is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
5
8
0
3
Order By: Relevance
“…Contrary to the results of research by Abdullah, Parvez, Karim, and Tooheen [19] that found that the stock return is significantly influenced by market capitalization. The same results were also obtained from the research by Kurniawan [20] and Wibowo, and Hendratno [21]. However, Taslim and Wijayanto [16] found that market capitalization has an insignificant negative effect on stock return.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Contrary to the results of research by Abdullah, Parvez, Karim, and Tooheen [19] that found that the stock return is significantly influenced by market capitalization. The same results were also obtained from the research by Kurniawan [20] and Wibowo, and Hendratno [21]. However, Taslim and Wijayanto [16] found that market capitalization has an insignificant negative effect on stock return.…”
Section: Introductionsupporting
confidence: 80%
“…The third result is that market capitalization has a significant negative effect on stock return. This result is in line with the research by Ardiansyah and Amanah [17], but contradicts with the researches by Kurniawan [20], Abdullah et al [19] and Wibowo, and Hendratno [21]. The negative effect is due to an increase in market capitalization is caused by an increase in stock prices.…”
Section: Discussionsupporting
confidence: 57%
“…To see whether an event contains abnormalities or not, event study method research is used. Event study is research by studying the market reaction to an event whose information is published as an announcement by taking a sample in the form of closing stock prices (Niawaradila et al, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…Market capitalization, as outlined by Niawaradila et al (2021), results from multiplying the closing market price by the total issued shares. Indari (2016) further proposed that market capitalization reflects the total value of a company, making it a crucial measure of a public company's success, economic significance, diversification potential, comparability, and liquidity.…”
Section: Capitalization Of Jiimentioning
confidence: 99%
“…Investors often consider market capitalization when deciding to invest in a particular stock. High capitalization stocks, according to Novirman in Niawaradila et al (2021), are particularly attractive to investors due to their above-average industrial capabilities. Investors tend to hold these stocks because they have financial stability and reliability.…”
Section: Capitalization Of Jiimentioning
confidence: 99%